(untitled) (Global Journal of Science Frontier Research, 2022)
Two great physicists of our time-academicians Nikolai Basov and Alexander Prokhorov in recent interviews said that they managed to significantly advance laser physics, which they also discovered and developed. But nevertheless, it has not yet become possible to create a strategic laser weapon (LW). They passed this baton to the students. Today, assessing what was done then in the conditions of acute competition with the United States, I want to confirm the validity of what Academician Andrey Kokoshin said: "Laser technology, like space and nuclear technologies, was a powerful catalyst for the scientific and technological progress of the country." And here it is more than appropriate to recall together with the Nobel laureates another outstanding creator. This progress was made by Dmitry Ustinov, who in 1969 insisted on making an important decision to establish the NPO Astrophysics -a leading scientific center of the country focused on the development of the element base of high-power and high-energy LW and related laser technologies /1/.